2008
DOI: 10.1093/aje/kwn294
|View full text |Cite
|
Sign up to set email alerts
|

Light to Moderate Alcohol Consumption and Disability: Variable Benefits by Health Status

Abstract: In adults, light to moderate alcohol consumption is associated with lower risks for heart disease, diabetes, and mortality. This study examined whether light to moderate alcohol use is also associated with lower risk of incident physical disability over two 5-year periods in 4,276 noninstitutionalized adults in the United States, aged 50 years or older, by using data from 3 waves of the National Health and Nutrition Examination Survey Epidemiologic Follow-up Study surveys from 1982 to 1992. Light/moderate drin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 35 publications
0
29
0
Order By: Relevance
“…Given recent encouragement of light drinking for health benefi ts (Britton et al, 2008;Ferreira and Weems, 2008;French and Zavala, 2007;Karlamangla et al, 2009), we consider examination of unforeseen negative consequences of alcohol consumption an important avenue of continued research (Ngandu et al, 2007;Oscar-Berman and Marinkovic, 2007). In this study, we compared midlife cognition of individuals who met criteria for a lifetime alcohol diagnosis with individuals who did not.…”
mentioning
confidence: 99%
“…Given recent encouragement of light drinking for health benefi ts (Britton et al, 2008;Ferreira and Weems, 2008;French and Zavala, 2007;Karlamangla et al, 2009), we consider examination of unforeseen negative consequences of alcohol consumption an important avenue of continued research (Ngandu et al, 2007;Oscar-Berman and Marinkovic, 2007). In this study, we compared midlife cognition of individuals who met criteria for a lifetime alcohol diagnosis with individuals who did not.…”
mentioning
confidence: 99%
“…13218 Evidence on alcohol consumption and disability has been mixed. 15,19 Moderate alcohol consumption may have a protective effect for general physical functioning, but high consumption may be harmful. 20 While this study does not specifically assess the impact of initiating alcohol consumption, it suggests that efforts to reduce alcohol consumption may not improve ADL outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…This finding contradicts observations in the literature showing a higher proportion of alcohol abuse among individuals with chronic illnesses 10,43 . Other studies have shown health benefits from alcohol consumption, but such protection only holds true with light-to-moderate drinking 10,50 .…”
Section: Discussionmentioning
confidence: 99%